Proposta curricular do estado de Minas Gerais: uma análise pela ótica de professores e alunos do ensino médio - Russo, Alexandre Antonio (2013)
When starting the study of Chemistry Basics, we use the knowledge and knowledge that students already have and they often do not relate to chemistry, and promote thus a connection between scientific knowledge and the experience of them. Thus diagnose the need for implementation of a New Curriculum Proposal, to meet the needs of new teaching and learning processes that produce knowledge for high school students, improving school performance. Therefore, one must seek the meaning of the chemical concepts, from experimentation, interactive lessons and the use of information technology for obtaining these concepts, thus providing the student performing and interpreting experiments, forming a link between theory and practice. For this we turn to the New Curriculum Proposal - Content Chemistry of Common Basic, designed and implemented by the SEE / MG, with the prospect of developing new skills to teach, meet the demands generated by the use of new technologies, encouraging conduct research in all sources of information available, due to the variety of approaches and especially the update of the available themes. It is expected that there is an involvement of students so that they are producers and not mere consumers of technology, promoting the enhancement of interaction between students / pupils, students / teachers and teachers / teachers, from the exchange of experiences, cooperation and joint construction by paths that seem to emphasize the development of higher mental processes as opposed to memorization and retention of information, providing them means that they raise hypotheses, seek discovery and reasoning, expand your creativity to facilitate the integration of different content and use the technology to research as tools for the development of knowledge. This proposal, which may contribute to the improvement of teachers' work and their relationships with the students raised the interest and greater involvement in the construction of knowledge, renewing the way to address the diverse content. To achieve this goal, they were used for data collection instruments, an initial diagnostic evaluation and another end, an evaluation questionnaire with 14 questions. For teachers was also applied a questionnaire of 11 questions to assess the level of knowledge and involvement in the content of Chemical Common Basic. This research proposes a reflection on the implementation, results and the direction on the New Curriculum Proposal.